THE GEOECOLOGICAL IMPACT ASSESSMENT OF GAS MAINS ON THE VALLEY IN PRECARPATHIAN REGION - Адаменко, Олег Максимович; Адаменко, Олег Ярославович; Шкіца, Леся Євстахіївна; Мандрик, Олег Михайлович; Міщенко, Лариса Володимирівна; Зорін, Денис Олександрович; Міщенко, Анастасія В’ячеславівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The article deals with the problem of gas mains’ influence on valley through ecological and geochemical studies of soils, surface and groundwater, air and vegetation. It has been defined areas of different ecological condition. It is made the estimation of ecological situation of the Bogorodchany district.